The simplicity of the Hodge bundle - Anand Patel (Proceedings of the National Academy of Sciences, 2026)
This paper establishes the simplicity of the Hodge bundle, a theorem in the branch of modern mathematics known as algebraic geometry. Notably, the essential mathematical content was autonomously generated by Aletheia, a custom AI agent powered by Gemini Deep Think.